2016
DOI: 10.1038/nrendo.2016.88
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus: does an effective prevention strategy exist?

Abstract: The overall incidence of gestational diabetes mellitus (GDM) is increasing worldwide. Preventing pathological hyperglycaemia during pregnancy could have several benefits: a reduction in the immediate adverse outcomes during pregnancy, a reduced risk of long-term sequelae and a decrease in the economic burden to healthcare systems. In this Review we examine the evidence supporting lifestyle modification strategies in women with and without risk factors for GDM, and the efficacy of dietary supplementation and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 86 publications
(99 reference statements)
2
83
0
3
Order By: Relevance
“…Antenatal interventions to prevent these consequences appear to have limited benefits. Exercise has the potential to promote greater maternal insulin sensitivity, but its benefits during pregnancy are debated 113,114 . A recent Cochrane review failed to demonstrate that dietary and lifestyle (including exercise) interventions for women with gestational diabetes mellitus restored glycaemic control or prevented adverse effects for women or their babies 113,115 .…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Antenatal interventions to prevent these consequences appear to have limited benefits. Exercise has the potential to promote greater maternal insulin sensitivity, but its benefits during pregnancy are debated 113,114 . A recent Cochrane review failed to demonstrate that dietary and lifestyle (including exercise) interventions for women with gestational diabetes mellitus restored glycaemic control or prevented adverse effects for women or their babies 113,115 .…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
“…Exercise has the potential to promote greater maternal insulin sensitivity, but its benefits during pregnancy are debated 113,114 . A recent Cochrane review failed to demonstrate that dietary and lifestyle (including exercise) interventions for women with gestational diabetes mellitus restored glycaemic control or prevented adverse effects for women or their babies 113,115 . Although two reports have suggested some modest benefits of antenatal exercise in obese women, its late timing in those with no regular pattern of physical activity before pregnancy seems likely to bring limited benefits 116,117 .…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is defined as hyperglycemia first detected during pregnancy, ultimately due to insufficient insulin production relative to the physiologic insulin resistance of pregnancy [5]. The level of maternal glucose that constitutes a risk for mother and fetus is much debated, and there is currently no international consensus on glucose thresholds for the diagnosis of GDM [6–8]. Effective antenatal lifestyle intervention to improve maternal glucose metabolism and reduce GDM risk is in high demand [9].…”
Section: Introductionmentioning
confidence: 99%
“…Trials published to date indicate that prenatal interventions combining diet and exercise reduce gestational weight gain but not GDM risk [10–13]. Few trials of antenatal diet and exercise have reported levels of glucose, insulin and insulin resistance [8]. These levels may give information about alterations in maternal metabolism that are not disclosed by simply reporting the incidence of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin treatment was administrated when dietary control could not achieve this goal. The babies of GDM group were diagnosed as macrosomia when their birth-weight was equal to or exceeded 4000 g [14,15]. Controls were from healthy volunteers without any health problems during their health checkups at the at the Obstetrics and Gynecology Department in Wuxi Maternity and Child Health Hospital.…”
Section: Samples and Screening Phasementioning
confidence: 99%